2008
DOI: 10.3354/ab00109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated pCO2 on early development in the mussel Mytilus galloprovincialis

Abstract: We investigated the effects of seawater equilibrated with CO 2 -enriched air (2000 ppm, pH 7.4) on the early development of the mussel Mytilus galloprovincialis. Mussel embryos were incubated for 144 h (6 d) in control and high-CO 2 seawater to compare embryogenesis, larval growth and morphology with ordinary light, polarized light, and scanning electron microscopy. Embryogenesis was unaffected by exposure to high-CO 2 seawater up to the trochophore stage, but development at the trochophore stage was delayed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 39 publications
(54 reference statements)
4
100
0
1
Order By: Relevance
“…More sensitive early life-history stages of M. edulis from the Skagerrak have been shown to respond differently to ocean acidification: fertilization success increased at reduced pH (induced by high pCO 2 ) whereas subsequent larval shell growth was negatively affected, albeit only slightly (Renborg and Havenhand, unpublished results). Similar small negative effects on larval shell growth have also been reported in populations of M. edulis from the North Sea (Gazeau et al 2010;Bechmann et al 2011), and in related Mytilus species around the world (Kurihara et al 2009;Gaylord et al 2011;Sunday et al 2011). Early reports of the effects of ocean acidification on shell growth in adult M. edulis showed negative impacts (Gazeau et al 2007), a result that contrasts with those of Melzner and co-workers in the Kiel fjord (Thomsen et al 2010;Melzner et al 2011), although the latter might be expected to be a result of local adaptation to seasonally low pH-especially at such extreme levels (Melzner et al 2009b;Thomsen et al 2010).…”
Section: Macrozoobenthossupporting
confidence: 79%
“…More sensitive early life-history stages of M. edulis from the Skagerrak have been shown to respond differently to ocean acidification: fertilization success increased at reduced pH (induced by high pCO 2 ) whereas subsequent larval shell growth was negatively affected, albeit only slightly (Renborg and Havenhand, unpublished results). Similar small negative effects on larval shell growth have also been reported in populations of M. edulis from the North Sea (Gazeau et al 2010;Bechmann et al 2011), and in related Mytilus species around the world (Kurihara et al 2009;Gaylord et al 2011;Sunday et al 2011). Early reports of the effects of ocean acidification on shell growth in adult M. edulis showed negative impacts (Gazeau et al 2007), a result that contrasts with those of Melzner and co-workers in the Kiel fjord (Thomsen et al 2010;Melzner et al 2011), although the latter might be expected to be a result of local adaptation to seasonally low pH-especially at such extreme levels (Melzner et al 2009b;Thomsen et al 2010).…”
Section: Macrozoobenthossupporting
confidence: 79%
“…Earliest studies on echinoderms found no effect on fertilisation of Hemicentrotus pulcherrimus and Echinometra mathaei, at pH 7.6 and 7.7 but at pH 6.8 for Hemicentrotus pulcherrimus and 6.8-7.1 Echinometra mathaei (−0.5 to −0.2 less than that predicted for 2300), there were significant effects with reduced fertilisation success and reduced cleavage speed in both species of sea urchins [52,53] and a trend for decreasing fertilisation with decreasing pH between 7.3-7.4 (Table S2). There were also no significant differences in fertilisation of the mollusc, Mytilus galloprovincialis, between controls and elevated CO 2 [57] and at pH 6.8-7.1 for Echinometra mathaei [53]. There was also decreased fertilisation success with increasing CO 2 concentrations for the coral, Acropora palmata [58].…”
Section: Fertilisationmentioning
confidence: 77%
“…A number of studies have found a delay in development or less development (the oysters Crassostrea gigas and Saccostrea glomerata [33,35,39]; the mussel M. galloprovincialis [57]; gastropod Littorina obtusata [63]), morphological shell abnormalities such as convex hinge and mantle protrusion and impacts on calcification size and growth rate (the oyster Crassostrea gigas [33,35,39]; the mussel M. galloprovincialis [57]; gastropod, Littorina obtusata shorter lateral, but longer spiral shell length [63] and Saccostrea glomerata [35,39,64]), decreases in shell length and thickness in the mussel (Mytilus edulis [65]), hatching rate (gastropod, Littorina obtusata [63], mussel Mytilus edulis [65]), degraded shells (mussel Mytilus edulis [65], polar pteropod Limacina helicina [66]) decreased rate of metamorphosis, shell thickness and loss of hinge integrity (bay scallop Argopecten irradians and the hard clam Mercenaria mercenaria [67]) and in the Mediterranean pteropod Cavolinia inflexa [68] shells were absent after 13 days due to dissolution, yet larvae displayed "normal" swimming action (Table S2). In rare instances there have been positive instead of negative impacts of elevated CO 2 .…”
Section: Molluscsmentioning
confidence: 99%
“…Havenhand et al (2008) studying the urchin Heliocidaris erythrogramma found statistically significant reductions in fertilization success at pH 7.7 (≈1000 ppm CO 2 ). Lastly, Kurihara et al (2007Kurihara et al ( , 2009 found no significant effect of 2000 ppm CO 2 (≈pH 7.4) treatments on fertilization success of the bivalves Crassostrea gigas and Mytilus galloprovincialis from Japan (although there were significant subsequent effects on larval development -see below).…”
Section: Introductionmentioning
confidence: 99%